Tele-supervised home-based transcranial alternating current stimulation (tACS) for Alzheimer’s disease: a pilot study - Cappon, Davide; Fox, Rachel; den Boer, Tim; Yu, Wanting; LaGanke, Nicole; Cattaneo, Gabriele; Perellón-Alfonso, Ruben; Bartrés-Faz, David; Manor, Brad; Pascual-Leone, Alvaro (Frontiers in Human Neuroscience, 2023)
Background Over 55 million people worldwide are currently diagnosed with Alzheimer’s disease (AD) and live with debilitating episodic memory deficits. Current pharmacological treatments have limited efficacy. Recently, transcranial alternating current stimulation (tACS) has shown memory improvement in AD by normalizing high-frequency neuronal activity. Here we investigate the feasibility, safety, and preliminary effects on episodic memory of an innovative protocol where tACS is administered within the homes of older adults with AD with the help of a study companion (HB-tACS). Methods Eight participants diagnosed with AD underwent multiple consecutive sessions of high-definition HB-tACS (40 Hz, 20-min) targeting the left angular gyrus (AG), a key node of the memory network. The Acute Phase comprised 14-weeks of HB-tACS with at least five sessions per week. Three participants underwent resting state electroencephalography (EEG) before and after the 14-week Acute Phase. Subsequently, participants completed a 2–3-month Hiatus Phase not receiving HB-tACS. Finally, in the Taper phase, participants received 2–3 sessions per week over 3-months. Primary outcomes were safety, as determined by the reporting of side effects and adverse events, and feasibility, as determined by adherence and compliance with the study protocol. Primary clinical outcomes were memory and global cognition, measured with the Memory Index Score (MIS) and Montreal Cognitive Assessment (MoCA), respectively. Secondary outcome was EEG theta/gamma ratio. Results reported as mean ± SD. Results All participants completed the study, with an average of 97 HB-tACS sessions completed by each participant; reporting mild side effects during 25% of sessions, moderate during 5%, and severe during 1%. Acute Phase adherence was 98 ± 6.8% and Taper phase was 125 ± 22.3% (rates over 100% indicates participants completed more than the minimum of 2/week). After the Acute Phase, all participants showed memory improvement, MIS of 7.25 ± 3.77, sustained during Hiatus 7.00 ± 4.90 and Taper 4.63 ± 2.39 Phases compared to baseline. For the three participants that underwent EEG, a decreased theta/gamma ratio in AG was observed. Conversely, participants did not show improvement in the MoCA, 1.13 ± 3.80 after the Acute Phase, and there was a modest decrease during the Hiatus −0.64 ± 3.28 and Taper −2.56 ± 5.03 Phases. Conclusion This pilot study shows that the home-based, remotely-supervised, study companion administered, multi-channel tACS protocol for older adults with AD was feasible and safe. Further, targeting the left AG, memory in this sample was improved. These are preliminary results that warrant larger more definite trials to further elucidate tolerability and efficacy of the HB-tACS intervention. NCT04783350. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04783350?term=NCT04783350&draw=2&rank=1, identifier NCT04783350.